Empire and Religion : Religious Change in Greek Cities under Roman Rule - Muñiz Grijalvo, Elena (Impact of Empire Ser, 2017)
Contents -- Introduction -- Chapter 1 Priesthoods and Civic Ideology: Honorific Titles for Hiereis and Archiereis in Roman Asia Minor -- Chapter 2 Public Sacrifice in Roman Athens -- Chapter 3 Cultic and Social Dynamics in the Eleusinian Sanctuary Under the Empire -- Chapter 4 Communication Between Sanctuaries and Rulers: An Analysis of Religious Resistance to Roman Abuses in the Greek East During the Roman Republic -- Chapter 5 Trajan and Hadrian's Reorganization of the Agonistic Associations in Rome -- Chapter 6 P.Oxy. 471: Hadrian, Alexandria, and the Antinous Cult -- Chapter 7 Hadrian Among the Gods -- Chapter 8 Some Thoughts on the Cult of the Pantheon ('All the Gods'?) in the Cities and Sanctuaries of Roman Greece -- Chapter 9 Emperor Worship and Greek Leagues: The Organization of Supra-Civic Imperial Cult in the Roman East -- Chapter 10 Le paysage culturel de la colonie romaine de Philippes en Macédoine : cosmopolitisme religieux et différentiation sociale -- Index Geographicus -- Index Nominum -- Index Rerum Sacrorum -- Index Rerum Memorabilium.